Optimal Control of Multi-Supplier Inventory Management with Lead Time - Darsih Idayani; Subchan Subchan (LPPM Institut Teknologi Sepuluh Nopember, 2020)
In the current global competition, companies are required to save money in order to survive. One of the expenses that can be reduced is the cost of inventory control. To minimize these costs, we require a proper planning and management of the inventory. Ordering supplies should be performed at a certain time period, especially with uncertain demand. As such, the company must determine when to order at the suppliers and how many should be ordered. So there will be no excess inventory in the warehouse because of too much ordering or because of the inventory cannot meet demand due to late or too little order to suppliers. Consequently, in this research, a quadratic cost functional is used as the objective function in multi-supplier inventory management problem with different lead time. Optimal control theory, LQR (Linear Quadratic Regulator) is used to solve this problem. According to the simulation, we conclude that the smaller weight resulted in more optimal inventory cost.